2008
DOI: 10.1542/peds.2007-2658
|View full text |Cite
|
Sign up to set email alerts
|

Serial Immune Markers Do Not Correlate With Clinical Exacerbations in Pediatric Autoimmune Neuropsychiatric Disorders Associated With Streptococcal Infections

Abstract: The failure of immune markers to correlate with clinical exacerbations in children with pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections raises serious concerns about the viability of autoimmunity as a pathophysiological mechanism in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 34 publications
4
54
0
3
Order By: Relevance
“…However, these combined cytokine clinical fluctuations were more frequent in the non-PANDAS than in PANDAS cases. In contrast, Singer et al (2008) found no association between clinical exacerbations (associated or not with GAS infection) and several effector molecules including both TNF-a and IL-12 (Singer et al 2008).…”
Section: Serologic and Prospective Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…However, these combined cytokine clinical fluctuations were more frequent in the non-PANDAS than in PANDAS cases. In contrast, Singer et al (2008) found no association between clinical exacerbations (associated or not with GAS infection) and several effector molecules including both TNF-a and IL-12 (Singer et al 2008).…”
Section: Serologic and Prospective Studiesmentioning
confidence: 85%
“…They also found that antibodies to pyruvate kinase reacted strongly with surface antigens of infectious strains of Streptococcus, and antibodies to streptococcal M proteins reacted with pyruvate kinase. However, increases in antibodies to aldolase C, enolase, and pyruvate kinase were not detected in serial serum specimens obtained during one of the prospective longitudinal studies described above (Kurlan et al 2008;Singer et al 2008). Methodological differences in the laboratory procedures and patient selection may account for some of the inconsistencies across studies (Martino et al 2009).…”
Section: Serologic and Prospective Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Indirect support of such a theory includes a significantly higher incidence of autoimmune disease in the mothers of children with tics (Murphy et al, 2010). Nevertheless, the existence of this etiological entity is extremely controversial based on both epidemiological and autoimmune studies (Kurlan, 1998(Kurlan, , 2004Singer and Loiselle, 2003;Kurlan and Kaplan, 2004;Singer et al, 2005b;Kurlan et al, 2008;Singer et al, 2008;Morris et al, 2009;Leckman et al, 2011).…”
Section: Etiologymentioning
confidence: 99%
“…Early reports demonstrated that the unique clinical presentation of the PANDAS subgroup was useful in determining which children would benefit from treatment with antibiotics (Murphy and Pichichero 2002) or immunomodulatory therapies Perlmutter et al 1999;Snider et al 2005), such as intravenous immunoglobulin (IVIG) and plasmapheresis (interventions that are not helpful for non-PANDAS tic disorders and OCD, respectively) (Hoekstra 2004;Nicolson et al 2000). In addition, cross-reactive autoantibodies were found in sera of acutely ill PANDAS patients (Kirvan et al 2006(Kirvan et al , 2007Swedo 1994); these autoantibodies were not present in convalescent samples or in samples obtained from patients with non-PANDAS OCD or tic disorders (Singer et al 2008).…”
Section: Introductionmentioning
confidence: 99%